Exploration of Applying Lego NXT and Arduino in Situated Engineering Teaching: A Case Study of a Robotics Contest at King Saud University - Haykel Marouani (Association for Scientific Computing Electronics and Engineering (ASCEE), 2022)
Saudi students in engineering courses suffer from a lack of science, technology, engineering, and mathematics (STEM) knowledge due to the teaching philosophy and programs offered in secondary and intermediate schools. This weakness naturally impacts their motivation, grades, and their relationship with teachers. In this paper, we introduce a new experimental teaching experience in the Applied Mechanical Department of the Applied Engineering College of King Saud University, based on situated learning theory, which emphasizes that knowledge must be learned in constructed situational context). This experience involved introducing Lego NXT and Arduino to enhance the enthusiasm and interest of students through designing and building robots in agreement with the “Introduction to design” course syllabus. Two experimental challenges were associated with: the line-follower problem and the maze problem. These challenges took the form of an internal completion at the end of each semester. The experience was conducted for two consecutive terms (30 students, the academic year 2019-2020), and the results were compared to those in six previous terms (100 students, academic years from 2016 to 2019). The experimental group demonstrated grades improvement (course mean grade rose from 77.1 to 85.3), the progress of academic achievement, and interest that enables them to actively explore and construct knowledge.